The AP-1 transcription factor Fra1 inhibits follicular B cell differentiation into plasma cells - Groetsch, Bettina; Brachs, Sebastian; Lang, Christiane; Luther, Julia; Derer, Anja; Schlötzer-Schrehardt, Ursula; Bozec, Aline; Fillatreau, Simon; Berberich, Ingolf; Hobeika, Elias; Reth, Michael; Wagner, Erwin F.; et al. (Journal of Experimental Medicine, 2014)
The cornerstone of humoral immunity is the differentiation of B cells into antibody-secreting plasma cells. This process is tightly controlled by a regulatory gene network centered on the transcriptional repressor B lymphocyte-induced maturation protein 1 (Blimp1). Proliferation of activated B cells is required to foster Blimp1 expression but needs to be terminated to avoid overshooting immune reactions. Activator protein 1 (AP-1) transcription factors become quickly up-regulated upon B cell activation. We demonstrate that Fra1, a Fos member of AP-1, enhances activation-induced cell death upon induction in activated B cells. Moreover, mice with B cell-specific deletion of Fra1 show enhanced plasma cell differentiation and exacerbated antibody responses. In contrast, transgenic overexpression of Fra1 blocks plasma cell differentiation and immunoglobulin production, which cannot be rescued by Bcl2. On the molecular level, Fra1 represses Blimp1 expression and interferes with binding of the activating AP-1 member c-Fos to the Blimp1 promoter. Conversely, overexpression of c-Fos in Fra1 transgenic B cells releases Blimp1 repression. As Fra1 lacks transcriptional transactivation domains, we propose that Fra1 inhibits Blimp1 expression and negatively controls plasma cell differentiation through binding to the Blimp1 promoter. In summary, we demonstrate that Fra1 negatively controls plasma cell differentiation by repressing Blimp1 expression.
EVALuna2:13013